Analisis Framing Postingan Gibran Selama Debat Presiden/Wakil Presiden di Akun Instagram kompas.com dan kumparan.com: Analisis Framing Postingan Gibran Selama Debat Presiden/Wakil Presiden di Akun Instagram kompas.com dan kumparan.com - Muryanti (Jurnal Sosiologi Nusantara, 2024)
The presidential and vice-presidential elections in 2024 have gained multiple controversies due to the violation of the constitution by Gibran Rakabuming Raka during his run as vice-presidential candidate. The violation is related to the age limit that defies the constitution.This violation becomes the subject and source of the main problem. This research aims to find out what are the comments from the followers of Kompas.com and Kumparan.com on Instagram on the posts about Gibran during the multiple presidential/vice-presidential debates. The data sampling is conducted in the two social media accounts since both accounts have more than one million followers and the data posted is recognized to be accurate. The theory used is the Framing Analysis from Robert N. Entman which, in the analysis process, uses four steps of analysis: defining the problem, estimating the source of the problem, creating a moral decision, and emphasizing problem-solving. The findings of the research show that the main source of problem of this candidature is the violation of the constitution by Gibran since he has not reached the candidature age limitation of 40 years old. The violation of age limitation becomes a pressure point that anything that Gibran did during the debate process is related to the violation of ethics. Gibran is considered to have violated ethics during the presidential/vice-presidential debates, among them : using gimmicks considered as bringing down, mocking, insulting, and impolite, such as moving his hands and body when looking for Mahfud MD’s answers, alongside spewing statements mocking his opponents, The solution offered for violation of ethics by Gibran or other candidates is by reporting them to The General Election Supervisory Agency (BAWASLU) if there are any fraud or foul play conducted by any candidates of the election.